Information management for clinical and evidence-based medical librarianship - Valera, Francisco Jose S.; Aguirre, Vyva Victoria M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
Evidence-based medicine is defined as "the conscientious explicit, and judicious use of current best evidence in making decisions about the care of individual patients" (Sackett, 1996). This study entitled "Information Management for Clinical and Evidence-based Medical Librarianship" is meant to explore the various problems librarians face in dealing with information for medical professionals. This study focused on 4 objectives namely: 1) To evaluate the receptiveness of medical professionals in the Philippines to evidence-based medicine; 2) To define the role of the medical librarian in information management that will support evidence-based medicine; 3) To evaluate the readiness of our medical librarians with regards to information management in supporting evidence-based medicine, and, 4) To evaluate the tools and techniques they have and they utilize and to see if these are sufficient in addressing the medical professionals' current and future information needs.
This study includes medical libraries of University of the Philippines-Manila (UP-Manila), University of the East Ramon Magsaysay Memorial Medical Center (UERMMMC), University of Santo Tomas (UST) and Ateneo School of Medicine and Public Health (ASMPH). The respondents of the study are the head librarians of the mentioned institutions and 10 doctors each from the same institutions. The study uses two sets of questionnaires as main research instruments in gathering information. The first questionnaire, for medical professionals, focuses mainly on the study by Mayer and Piterman in 1999 entitled The Attitudes of Australian GPs to Evidence-Based Medicine : a Focus Group Study. Three simple questions are derived from the study for Gavgani in 2008 entitled Physicians' Attitude towards Evidence-Based Medical Practice and Health Sciences Library Services. The other questionnaire, which is for librarians, is based on Evidence-Based Librarianship: the EBL Process from the study of Eldredge in 2006.
The results led to the following conclusions: 1) Medical professionals are receptive to evidence-based medicine; 2 The role of medical librarians in here in the Philippines are not much different from the role of other academic librarians; however, 3) Medical librarians already practice evidence-based librarianship, although they are not aware of it; and 4) Medical databases in respondent libraries are sufficient for the current information needs of medical professionals as attested to by the database usage statistics of the four medical institutions.
Recommendations include: 1) A similar study but involving hospital libraries is recommended since there should be more medical professionals involved because it would also give clearer results and not just trends compared to this study; 2) Medical librarians should be given greater roles in clinical and evidence-based medical librarianship; and 3) Databases should be linked to other medical schools as part of resource sharing similar to a consortium which is beneficial to the improvement of evidence-based medicine.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Evidence-based medicine -- Philippines; Physicians -- Philippines -- Manila; Physicians -- Philippines -- Quezon City; Physicians -- Philippines -- Mandaluyong City; Medical librarians -- Philippines -- Manila; Medical librarians -- Philippines -- Quezon City; Medical librarians -- Philippines -- Mandaluyong City